Giving to God - Mittermaier, Amira, 1974- (Oakland, California)
xiv, 233 sayfa
Keywords: “Giving to God examines the everyday practices of Islamic giving in post-revolutionary Egypt. From foods prepared in Sufi soup kitchens, to meals distributed by pious volunteers in slums, to almsgiving, these acts are ultimately about giving to God by giving to the poor. Surprisingly, many who practice such giving say that they do not care about the poor, instead framing their actions within a unique non-compassionate ethics of giving. At first, this form of giving may appear deeply selfish, but further consideration reveals that it avoids many of the problems associated with the idea of “charity.” Using the Egyptian uprising in 2011 and its call for social justice as a backdrop, this beautifully crafted ethnography suggests that “giving a man a fish” might ultimately be more revolutionary than “teaching a man to fish”“ --